1984
DOI: 10.1143/jjap.23.544
|View full text |Cite
|
Sign up to set email alerts
|

Static SIMS Investigation of Ag-Supported Amino Acids

Abstract: The static mode of secondary-ion mass-spectroscopy (static SIMS) was used to investigate Ag-supported amino acids, the amount of amino acids on the Ag surface being systematically controlled. It is shown in this report that a mono-molecular layer (full coverage θ=1) is produced at a surface concentration of about 5×1014 molecule/cm2. The possibility of the quantitative detection of amino acids with static SIMS for θ<1 is also demonstrated. The fact that the ratio (M-COOH)+/(M+H)+ from a mixture of two amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…By using an atomic primary ion, quasimolecular secondary‐ion signals were most strongly observed for [ M H−SH−COOH] + ( m / z 1085.61 for P Abl and m / z 857.52 for P Abl−s ) instead of [ M H] + , as shown in Figure 2 a and b. This result indicated that the cysteine sulfhydryl group (SH) was strongly attached onto the surface of the AuNPs by a thiol bond,7 and molecular ion signals with the subtraction of a carboxylic acid group reflect one of the sputtering features in amino acid analysis with SIMS 8…”
mentioning
confidence: 83%
“…By using an atomic primary ion, quasimolecular secondary‐ion signals were most strongly observed for [ M H−SH−COOH] + ( m / z 1085.61 for P Abl and m / z 857.52 for P Abl−s ) instead of [ M H] + , as shown in Figure 2 a and b. This result indicated that the cysteine sulfhydryl group (SH) was strongly attached onto the surface of the AuNPs by a thiol bond,7 and molecular ion signals with the subtraction of a carboxylic acid group reflect one of the sputtering features in amino acid analysis with SIMS 8…”
mentioning
confidence: 83%
“…Beyond 4 mg/mL, a drastic yield decrease is observed. Another work conducted with amino-acids [13] reported a linear relationship between the SI yield and the surface concentration ranging from 1 ϫ 10 13 to 5 ϫ 10 14 arginine molecule/cm 2 . The authors attributed these results to a complete monolayer of arginine being formed with 5 ϫ 10 14 molecule/cm 2 .…”
Section: Yield Variations As a Function Of The Ps Layer Thicknessmentioning
confidence: 97%
“…Without metallization, the effect of the PS sample concentration on the characteristic secondary ion yields is dramatic and strongly dependent on the chosen projectile type (Figure 2). For atomic projectile bombardment, maximums in the yield versus concentration curves have been already reported for polymers such as PS [11], PMMA [12,26], PVC [12], and for biological films [13]. Norrman et al [12] spin-coated PMMA and PVC on Si wafers using a range of polymer concentrations.…”
Section: Yield Variations As a Function Of The Ps Layer Thicknessmentioning
confidence: 99%
“…The mechanisms, however, are various, sample specific and difficult to model. Many molecules, especially polar species like amino acids 80,81 and amphiphile molecules, 82 ionize through the addition or loss of a proton, forming (M À H) À and (M þ H) 1 parent-like ions. As a function of their acid/base character they tend to aggregate with a cation or release a proton upon ejection.…”
Section: Ionization Of An Organic Samplementioning
confidence: 99%